PENGARUH PERSIAPAN PAGELARAN SENI AMERTA TERHADAP HASIL BELAJAR TAFSIR SISWA KELAS XII DI PONDOK PESANTREN TAHFIDZUL QUR'AN ABI UMMI AMPEL BOYOLALI TAHUN AJARAN 2024/2025 - Taqiya, Zidny; Rochmawan, Alfian Eko; Sarjono, Joko (Institut Islam Mamba'ul 'Ulum Surakarta, 2025)
The purpose of this study is to determine the effect of the preparation of the Amerta Art Performance on the Tafsir learning outcomes of 12th-grade students at PPTQ Abi Ummi Boyolali for the 2024/2025 academic year. This study adopted a quantitative method, involving 75 12th-grade students as the sample. Data were collected by using questionnaires and documentation techniques. Data analysis employed statistical techniques, including validity and reliability tests to ensure the data's consistency. The results of the study show that the preparation of the Amerta Art Performance is categorized as good, with a percentage of 46.66%. Meanwhile, the Tafsir learning outcomes are categorized as low, with a percentage of 40%. Hypothesis testing using the product-moment correlation formula produced a correlation coefficient (rxy) of 0.375. This value indicates a weak but significant correlation between the preparation of the Amerta Art Performance and Tafsir learning outcomes. Since the value of rxy is greater than rtabel, which is 0.227 at a 95% significance level, the hypothesis is accepted.